(untitled) (Revista de Crítica Literaria Latinoamericana, 2023)
This article analyzes the representation of death, both in lifeless bodies and in their meanings and relationships established with corpses, in three fictions: the novels La transmigración de los cuerpos by Yuri Herrera (Periférica, 2013) and Lobo by Bibiana Camacho (Almadía, 2017), as well as the short story “El dolor los vuelve ciegos” by Eduardo Ruiz Sosa (in Cuántos de los tuyos han muerto, Candaya 2019). For this purpose I will carry out a close reading of the narrations and I will rely mainly on bio/necro-political reflections of both historical-political-philosophical and artistic nature.